Biochemical Bone Turnover Markers and Osteoporosis in Older Men: Where Are We? - Pawel Szulc (Journal of Osteoporosis)
In men aged less than 60, the association of serum and urinary levels of biochemical bone turnover markers (BTMs) and bone mineral density (BMD) is weak or not significant. After this age, higher BTM levels are correlated weakly, but significantly, with lower BMD and faster bone loss. Limited data from the cohort studies suggest that BTM measurement does not improve the prediction of fragility fractures in older men in comparison with age, BMD, history of falls and fragility fractures. Testosterone replacement therapy (TRT) decreases bone resorption. During TRT, bone formation markers slightly increase (direct effect on osteoblasts), then decrease (slowdown of bone turnover). Bisphosphonates (alendronate, risedronate, ibandronate, zoledronate) induce a rapid decrease in bone resorption followed by a milder decrease in bone formation. In men receiving antiresorptive therapy for prostate cancer, zoledronate, denosumab and toremifene decrease significantly levels of bone resorption and bone formation markers. Teriparatide induced a rapid increase in serum concentrations of bone formation markers followed by an increase in bone resorption. We need more studies on the utility of BTM measurement for the improvement of the persistence and adherence to the anti-osteoporotic treatment in men.